2018
DOI: 10.1016/j.nicl.2018.06.015
|View full text |Cite
|
Sign up to set email alerts
|

Brain lesion scores obtained using a simple semi-quantitative scale from MR imaging are associated with motor function, communication and cognition in dyskinetic cerebral palsy

Abstract: PurposeTo characterise brain lesions in dyskinetic cerebral palsy (DCP) using the semi-quantitative scale for structural MRI (sqMRI) and to investigate their relationship with motor, communication and cognitive function.Materials and methodsThirty-nine participants (19 females, median age 21y) with DCP were assessed in terms of motor function, communication and a variety of cognitive domains. Whole-head magnetic resonance imaging (MRI) was performed including T1-MPRAGE, T2 turbo spin echo (axial plane), and fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 40 publications
2
18
1
Order By: Relevance
“…However, the global total brain score in the total group did not correlate to the GMFCS. This is contradictory with recent findings in dyskinetic CP, where the global brain score was found to be a significant predictor for the GMFCS (Laporta-Hoyos et al, 2018). This difference might stem from several factors.…”
Section: Brain Structure -Motor Function Relationshipcontrasting
confidence: 99%
See 2 more Smart Citations
“…However, the global total brain score in the total group did not correlate to the GMFCS. This is contradictory with recent findings in dyskinetic CP, where the global brain score was found to be a significant predictor for the GMFCS (Laporta-Hoyos et al, 2018). This difference might stem from several factors.…”
Section: Brain Structure -Motor Function Relationshipcontrasting
confidence: 99%
“…In the present study, only approximately 10% of the patients presented with such low global brain scores. Lastly, the total group in this study showed an equal distribution between bCP and uCP children, whereas the study of Laporta-Hoyos et al (2018) included mostly bCP dyskinetic children (Laporta-Hoyos et al, 2018).…”
Section: Brain Structure -Motor Function Relationshipmentioning
confidence: 79%
See 1 more Smart Citation
“…In another cohort of 56 patients with dyskinetic CP, many different cerebral lesions were likewise seen, and the authors report a normal MRI in 9.8% with the most frequent injuries seen in white matter (26.8%) and grey matter (31.7%) . In another cohort of 39 patients with dyskinetic CP, where images were re‐evaluated systematically with focus on basal ganglia, brain lesions were most frequently located in the ventral posterior lateral thalamus and frontal lobe . It is likely that the use of a standardised imaging protocol and central review of images would have affected the imaging results.…”
Section: Discussionmentioning
confidence: 99%
“…Equipped also with advanced radiomics, researchers have made unprecedented progress in discovering biomarkers that can increasingly enable identification of individual patients (6)(7)(8)(9). However, it is still much more challenging to identify patients who will have effective treatment response (10,11). Using these biomarkers to make individual predictions of future treatment responses in the early phase of CP will be clinically important.…”
Section: Introductionmentioning
confidence: 99%